Write a rule to the sequence.

8, -1, -10, -19, …

The sequence appears to be decreasing by 9 each time. So, the rule for the sequence is to subtract 9 from the previous term to get the next term. Therefore, the rule is:

a(n) = a(n-1) - 9, where a(1) = 8.

Using this rule, the next few terms in the sequence would be:

a(5) = a(4) - 9 = -19 - 9 = -28
a(6) = a(5) - 9 = -28 - 9 = -37

To determine the rule for the given sequence, let's analyze the differences between consecutive terms:

-1 - 8 = -9
-10 - (-1) = -9
-19 - (-10) = -9

We observe that the differences between consecutive terms are always -9. Therefore, the rule for this sequence can be expressed as follows:

Start with 8 and subtract 9 from the previous term to get the next term.

So, the next term in the sequence would be:

-19 - 9 = -28